Improved Ability to Recognize Letters Through Flashcard Media With Maximization Memory for Children With Autistic Special Needs - Subaihah, Yani Yustika; Alfinuha, Setyani; Hasanah, Muhimmatul; Indrawati, Intan (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
Generally, the difficulties experienced by autistic children are basic academic abilities, namely reading, writing, and arithmetic. Autistic children often experience attention disorders so that in the learning process children are easily bored to learn. Therefore, learning media is needed that can make children excited about learning. The Flashcard media program is carried out by focusing on strengthening memory at the beginning, according to Rasto's theory, the initial stage of beginner reading is to use Visual Memory. Muses single-subject research with the form of A-B-A program design. Basedon the results of the program, the use of Flashcards with memory maximization methods can help children recognize letters as a basic step to meet the first stage in beginner reading With the pretest that originally could only spell 2 letters, after intervening against the increase to 9 letters at the time of posttest.